ANALISIS BIAYA-MANFAAT DAN APLIKASI MODEL PENERIMAAN TEKNOLOGI PADA KEPUTUSAN OUTSOURCING TI - Rahmiati, Rahmiati (Performance, 2009)
Information technology outsourcing continues to advance. Outsourcing can be success if it’s done for the right reason, follow due process, and it pursued with realistic expectation and a clear understanding of where the benefits are likely to emerge. Although interest to outsourcing arise, but many companies have no a clear understanding about the consequency. This article try to give an overview about cost, risk and benefit of Information Technology outsourcing